A> Metode Teknik Pair Share Bagi Siswa Kelas V SDN Yosowilangun Kecamatan Manyar Kabupaten Gresik Sebagai Upaya Meningkatkan Hasil Belajar Matematika - chotimah, Nanik Siti; Hidayati, Fitria (JURNAL WAHANA PENDIDIKAN DASAR, 2016)
In general formulation of the problem in the proposed PTK is: is think pair share learning method can improve the process of learning math class V SDN Yosowilangun Manyar District of Gresik? In particular formulation of the problem in the proposed PTK is described as follows: 1) Is the method of learning think pair share can improve the process and result of learning math class V SDN Yosowilangun Manyar District of Gresik? 2) Is the method of learning think pair share can improve the process and result of learning mathematics affective aspect or attitude class V SDN Yosowilangun Manyar District of Gresik? 3) Is the method of learning think pair share can improve the process and results of learning the mathematical aspect of psychomotor or cooperative skills class V SDN Yosowilangun Manyar District of Gresik. The subjects of this research in this PTK is a fifth grade students who will be drawn at random from the whole class V semester of the 2014/2015 academic year 1. The material taught is KD 1. Using a property that arithmetic operations. Researcher is a teacher at SDN Yasowilangun Manyar District of Gresik in the academic year 2014/2015 and the teaching of mathematics. Appropriate formulation of the problem ad research objectives, in general it can be concluded that the result for student at SDN Yosoilangun Manyar Diatrict of Gresik, can be increased through learning by using method think pair share, result ffor students of class V SDN Yosowilangu Manyar District of Gresik, the material Mathematics Basic competencies using arithmetic operating properties and can be increased significantly after implementation of learning activities through methods think pair share.